2021
DOI: 10.1038/s41541-021-00295-7
|View full text |Cite
|
Sign up to set email alerts
|

Highly pathogenic avian influenza A/Guangdong/17SF003/2016 is immunogenic and induces cross-protection against antigenically divergent H7N9 viruses

Abstract: Avian influenza A(H7N9) epidemics have a fatality rate of approximately 40%. Previous studies reported that low pathogenic avian influenza (LPAI)-derived candidate vaccine viruses (CVVs) are poorly immunogenic. Here, we assess the immunogenicity and efficacy of a highly pathogenic avian influenza (HPAI) A/Guangdong/17SF003/2016 (GD/16)-extracted hemagglutinin (eHA) vaccine. GD/16 eHA induces robust H7-specific antibody responses in mice with a marked adjuvant antigen-sparing effect. Mice immunized with adjuvan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…Our results demonstrated that Alum/CpG 1018-adjuvanted WV vaccines may be more potent cross-protect against the Anhui strain than the Alum-adjuvanted WV vaccine. Consistent with a previous study [ 51 ], an AddaVax-adjuvanted H7 vaccine derived from A/Guangdong/17SF003/2016 provided cross-reactivity and protection against Anhui-like H7N9 challenge in mice. However, we found that neither the Alum/CpG 1018- nor the Alum-adjuvanted WV vaccines provided cross-protection against the recently emerged H7N9 A/Gansu/23277/2019 virus.…”
Section: Discussionsupporting
confidence: 91%
“…Our results demonstrated that Alum/CpG 1018-adjuvanted WV vaccines may be more potent cross-protect against the Anhui strain than the Alum-adjuvanted WV vaccine. Consistent with a previous study [ 51 ], an AddaVax-adjuvanted H7 vaccine derived from A/Guangdong/17SF003/2016 provided cross-reactivity and protection against Anhui-like H7N9 challenge in mice. However, we found that neither the Alum/CpG 1018- nor the Alum-adjuvanted WV vaccines provided cross-protection against the recently emerged H7N9 A/Gansu/23277/2019 virus.…”
Section: Discussionsupporting
confidence: 91%
“…For titer and avidity determination, genes coding H3 HK HA, chimeric HA bearing H1 A/Puerto Rico/8/1934 stalk (group 1) with mismatched H16 HA head and chimeric HA bearing H3 HK stalk (group 2) with mismatched H4 HA head were synthesized as previously described (Stevens et al, 2004;Pica et al, 2012;Radvak et al, 2021)…”
Section: Recombinant Proteinsmentioning
confidence: 99%